STORAGE ROOM TEMPERATURE AND HUMIDITY MONITORING IOT- BASED MEDICINE - Mohamad Adnan Fauzi; Rahmat Hidayat; Taufik Hidayat (Department of Computer Engineering, Universitas Wiralodra, 2023)
This research is important as it portrays a notable advancement in current internet technology known as the Internet of Things (IoT), which facilitates advanced services through the interconnection of physical and virtual objects. One crucial aspect of everyday life is air quality, especially indoors, as indoor air pollution differs from outdoor air pollution. An important indicator to determine the cleanliness of a room is its humidity level. In this context, this research holds significant relevance as it can help ensure the effectiveness and safety of stored medications under appropriate temperature and humidity conditions. Therefore, this study designed a drug storage room that requires a tool to measure the humidity value of the room in real time and the humidity conditions in the room. The solution to this problem can be overcome using Internet of Things technology. In this project, a hygrometer, or humidity meter, based on Internet of Things technology is made. Humidity is measured by the DHT-11 sensor, which is integrated on the NodeMCU ESP8266 board. Humidity measurement data can be observed via the Blynk IoT platform available on smartphones. With this tool, humidity can be observed in real time, even from a distance. The results of this study are that the tool can measure the temperature and humidity of the medicine room, and the tool can send humidity and temperature measurement data to the Blynk IoT and MIT APP Inventor servers. On the Blynk IoT website, the dashboard can display temperature, humidity, and drug safety measurement data in real time.